Enhancing Smallholder Farmers' Access to Seed of Improved Legume Varieties Through Multi-stakeholder Platforms Learning from the TLIII project Experiences in sub-Saharan Africa and South Asia - Akpo, Essegbemon; Ojiewo, Chris O.; Kapran, Issoufou; Omoigui, Lucky O.; Diama, Agathe; Varshney, Rajeev K. (Springer Nature, 2021)
This open access book shares the experiences of Tropical Legumes III (TLIII) project in facilitating access to seed of improved legume varieties to smallholder farmers through innovation platforms. It highlights practices and guiding principles implemented in eight developing countries of sub-Saharan Africa and South Asia. This book details key processes that respective teams employed to create an innovation space that delivers seed, other inputs, knowledge and financial services to agricultural communities and most importantly, the underserved farmers in remote areas of the drylands. It offers valuable insights into the pathway to establishing, promoting and operating innovation platforms to enhance the performance and competitiveness of legume crops' value chains, and addresses critical issues that must be considered to make innovation platforms more sustainable and attractive to beneficiaries. The book offers a wealth of practical insights for development workers, technical staff, and project managers. This publication is all about TLIII community of practice. It will definitely inspire other development workers and scientists to share their own experiences for others to learn from.